Socio-demographic Factors of Caries and Dental Fillings in Indonesia with a Geospatial Mapping Approach - Ayu Asri Lestari; Risqa Rina Darwita; Melissa Adiatman (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Untreated caries is one of the oral diseases that poses a significant burden in Indonesia. The perceived need for people to receive dental treatment is influenced by sociodemographic, economic, environmental, and healthcare service factors. The purpose of this study was to determine sociodemographic factors towards untreated caries and dental fillings in Indonesia, and then visualize them in geospatial mapping. Material and Methods: A cross-sectional study used secondary data from Basic Health Research 2018. A sample was 14.031 subjects, then classified based on WHO age group and sociodemographic factors. As gender, residence, educational level, employment status, and frequency of dental visits as independent variables. Then, the number of untreated caries and fillings is the dependent variable. The bivariate analysis was used to determine different factors. QGIS was used to visualize dependent variables in 26 provinces in Indonesia. Results and Discussions: There was a statistically significant difference (p<0.05) in the 35-44 years age group between females, rural residents, those with no schooling, and informal workers concerning untreated caries. Meanwhile, females, urban residents, college diploma holders, formal workers, and those with dental visits showed a tendency toward dental fillings. This result closely aligns with overlay mapping geospatial analysis. Conclusion: Sociodemographic characteristics had an impact on untreated caries and dental fillings, and should be considered to find out comprehensive strategies to improve oral health care.